Persepsi nasabah terhadap tingkat kualitas pelayanan Bank Syariah Indonesia Kantor Cabang Pembantu Karang Baru Aceh Tamiang - Nuria Ajijah; Zuliani, Rafiza; Alfian (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
The purpose of this research is to determine customer perceptions of the quality of service at BSI KCP Karang Baru Aceh Tamiang and to determine the factors that influence customer perceptions about the quality of service at KCP Karang Baru Aceh Tamiang. This research uses qualitative methods using 7 informants. Of the five indicators in service quality, only the tangible aspect is not optimally implemented by BSI KCP Karang Baru, giving rise to unfavorable perceptions from customers. This can be a separate input for BSI BSI KCP Karang Baru to improve service quality from a tangible aspect so that customer perceptions of service quality can be fulfilled perfectly and create positive perceptions. Based on various positive perceptions held by customers, there are factors that influence this, namely employee work speed, work accuracy and also friendliness. Meanwhile, the comfort factor has not been able to be met by BSI KCP Karang Baru. Employees have done their best to work quickly, precisely and also show friendliness, but customers still feel uncomfortable when they are in the bank for too long because there are very few chairs and the space is narrow Keywords: Perception, Level of Service Quality, Bank Syariah Indonesia